Accelerating universe in modified teleparallel gravity theory. Issue Volume 15:Issue S356(2019) (October 2019) - Sahlu, Shambel; Ntahompagaze, Joseph; Abebe, Amare; Mota, David F.
Abstract: This paper studies the cosmology of accelerating expansion of the universe in modified teleparallel gravity theory. We discuss the cosmology of f ( T, B ) gravity theory and its implication to the new general form of the equation of state parameter wTB for explaining the late-time accelerating expansion of the universe without the need for the cosmological constant scenario. We examine the numerical value of wTB in different paradigmatic f ( T, B ) gravity models. In those models, the numerical result of wTB is favored with observations in the presence of the torsion scalar T associated with a boundary term B and shows the accelerating expansion of the universe.